EFEKTIVITAS INFORMASI PERTANAHAN BERBASIS NOMOR OBYEK PAJAK (NOP) TERHADAP TRANSAKSI JUAL BELI TANAH DI KOTA SURAKARTA - SAMAD, AMRIANTO (Dinamika Hukum, 2018)
The background of the application of land information information based on Tax Object Number (NOP) to the land sale transaction in Surakarta City is obtaining an effective, efficient, and compatible Land Information System. The use of information technology for public services is a demand that must be provided by the government, including the Government of Surakarta. Information technology is a necessity of society because it not only helps communication and social interaction quickly, but also provides convenience in many ways. "As a service, we must provide convenience when providing community service,". In the city of Surakarta the cooperation of making Land Map Information Map Based Tax Number (NOP) between the Government of Surakarta City and Land Office has been started since 2013 until 2017. From this application can be obtained various available land information can be utilized for the establishment of Multi Gunna Land Information System . In 1 (one) NOP of the same spatially indicated plot, can provide land information (NOP, Status of Land Ownership, Name and Address of Taxpayer, Land Use, Spatial Plan (RTRW), Value of Land Value Zone, Value Sell Tax Object (NJOP), Important Place Name, and Location Photo). Research Methods is a type of empirical research that is the type of legal research that analyzes and assesses its work in society. This research was conducted to find out the effectiveness of land information based on Tax Object Number (NOP) to the service of Kelurahan Office in Surakarta City and to know the impact of land information based on Tax Object Number (NOP) to the market value of land market transaction in Surakarta City. Based on the result of this research, it is expected that the effectiveness of Land Information Based on Tax Object Number (NOP) at the Kelurahan Office in Surakarta City is needed, because the community and the bank need the land value in accordance with the market price in the field. The Impact of Land Information based on Tax Object Number (NOP) on the market value of land in the community in Surakarta City, very useful as the base of land purchase price. Keywords: Land Information System that is effective, efficient, and compatible